2017
DOI: 10.1155/2017/2689642
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Clinical Assessments of Segmental Maxillary Posterior Tooth Intrusion

Abstract: Objective. To compare chondroitin sulphate (CS) levels around maxillary second premolars, first molars, and second molars between the unloaded and the loaded periods and to measure the rates of intrusion of maxillary posterior teeth during segmental posterior tooth intrusion. Materials and Methods. In this prospective clinical study, 105 teeth (from 15 patients exhibiting anterior open bite and requiring maxillary posterior tooth intrusion) were studied. Competitive ELISA was used to detect CS levels. Dental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…(31) Despite the fact that some studies did not clearly specify it, the reported force magnitudes for upper molar intrusion ranged from 150 g (13)(14)(15) to 500 g (20,(32)(33)(34)(35)(36)(37)(38)(39) . In the present study, FEA employed a total applied total molar intrusive force of 200 grams (100 g buccal and 100 g palatal), which was consistent with earlier studies (20,(40)(41)(42) which concluded that; upper molar intrusion forces should be between 100 and 200 g. which also consistent with the finding of Furthermore, Kato and Kato (43) claimed that a force of 100 g was inadequate for posterior segment intrusion and that raising the force to 300 g allowed for progressive intrusion keeping in mind, this study considering posterior segment no single molar intrusion.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…(31) Despite the fact that some studies did not clearly specify it, the reported force magnitudes for upper molar intrusion ranged from 150 g (13)(14)(15) to 500 g (20,(32)(33)(34)(35)(36)(37)(38)(39) . In the present study, FEA employed a total applied total molar intrusive force of 200 grams (100 g buccal and 100 g palatal), which was consistent with earlier studies (20,(40)(41)(42) which concluded that; upper molar intrusion forces should be between 100 and 200 g. which also consistent with the finding of Furthermore, Kato and Kato (43) claimed that a force of 100 g was inadequate for posterior segment intrusion and that raising the force to 300 g allowed for progressive intrusion keeping in mind, this study considering posterior segment no single molar intrusion.…”
Section: Discussionsupporting
confidence: 76%
“…The force magnitude effective in posterior or intrusion had subjected to much debate in previous numerous studies as stated by Foot R et al 2014 (31) ; Tasanapanont J et al 2017 (40) used 50 gm per side; others used a force ranged from 100 to 200 gm for posterior segment intrusion (20,(41)(42)(43) ; arrange for 200-400 gm was suggested by . Kravitz ND et al 2007 (27) ; others used a heavier force range from 400 to 500 gm (31,38,39,51) , So in the present study we tested a force started by 75 gm buccal and 75 gm palatal.…”
Section: Discussionmentioning
confidence: 99%
“…17 Different authors used variable forces and reported different amounts of intrusion. The minimum intrusive force used was 50 g per side, 21 while the more commonly used forces ranged between 100 and 200 g. 13,14,22 On the other hand, Kato and Kato 23 suggested that a force of 100 g was insufficient for posterior segment intrusion and stated that increasing the force up to 300 g permitted progressive intrusion. Later, a range of 200 to 400 g for segmental posterior intrusion was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…3 Open bite malocclusion occurs when maxillary and mandibular teeth are not in contact. 4 Hypofunctional teeth cause atrophic changes in the periodontal ligament, a decrease in the number of periodontal fibers and blood vessels, and the periodontal space's narrowing. Periodontal space's narrowing occurs due to the apposition of the alveolar bone by an increase in Transforming Growth Factor β (TGFβ), causing tooth elongation.…”
Section: Introductionmentioning
confidence: 99%